2017
DOI: 10.1186/s12872-017-0497-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Anemia Syndrome and Survival among Heart Failure Patients in Tanzania: A Prospective Cohort Study

Abstract: BackgroundCardiorenal anemia syndrome (CRAS) is an evolving global epidemic associated with increased morbimortality and cost of care. The management of patients with CRAS remains a challenging undertaking worldwide and the lack of evidence-based clinical guidelines adds to the challenge. We aimed to explore the prevalence and survival rates of heart failure patients with CRAS in Tanzania.MethodsWe screened 789 patients and consecutively recruited 463 who met the inclusion criteria. Each participant underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(90 citation statements)
references
References 11 publications
10
78
1
1
Order By: Relevance
“…11 From a Canadian population-based study of new onset HF, 3% (362/12 065) of the patients had CRAS. 13 In another study, 22% (210/955) of the patients had CRAS. 13 In another study, 22% (210/955) of the patients had CRAS.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…11 From a Canadian population-based study of new onset HF, 3% (362/12 065) of the patients had CRAS. 13 In another study, 22% (210/955) of the patients had CRAS. 13 In another study, 22% (210/955) of the patients had CRAS.…”
Section: Discussionmentioning
confidence: 94%
“…12 In a small Tanzanian study, they found that 44% (202/455) of the patients had CRAS. 13 In another study, 22% (210/955) of the patients had CRAS. 14 In our study, we found that 27% patient population comes under the CRAS category, which is almost double the results we obtained from CHARM trial.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Cardiovascular disorders (CVD) are responsible for about one-third of all global mortality with over threequarters of deaths transpiring in the developing world [1]. In spite of the remarkable advances in novel screening techniques and therapeutic directions, the prognosis of heart failure (HF) remains strikingly poor around the globe particularly in the developing nations [2][3][4][5][6][7]. Owing to its chronic nature, clinical management of HF necessitate long-term use of several drugs to reduce morbidity [8][9][10] and mortality [11][12][13].…”
Section: Introductionmentioning
confidence: 99%